KINESIOLOGICAL EDUCATION IN TEACHER EDUCATION PROGRAMMES FOR PRIMARY EDUCATION TEACHERS AND EARLY CHILDHOOD AND PRESCHOOL EDUCATION TEACHERS IN THE REPUBLIC OF CROATIA (Fiep Bulletin - online, 2014)
The aim of the paper was to compare the syllabuses and the number of kinesiology courses on the curricula of teacher education programmes for primary and early childhood and preschool education teachers in the Republic of Croatia. Systematic observation of the curricula included six universities in the Republic of Croatia, i.e. their constituents whose main scope is the education of primary and early childhood and preschool education teachers. Examination of the curricula yielded data on the type of study programme that is implemented, the number of lessons for the obligatory kinesiology courses on the curriculum for the 2012/2013 academic year, the number of ECTS credits and the number of semesters in which the courses are taught. A comparative analysis was applied to establish possible differences in the syllabuses and the number of kinesiology courses in the teacher education curricula for primary and early childhood and preschool education teachers in the Republic of Croatia. The obtained results show that kinesiology courses on the curricula of higher education institutions that educate primary education teachers are relatively homogeneous and that there are minimal differences in the total annual number of hours. Comparing the results for early childhood and preschool education teachers, it is evident that the differences are relatively significant, and that neither of the curricula have the same number of hours. Three faculties have university undergraduate studies, while at the other three faculties education is conducted at a professional level, and because of this, there are also significant differences in the number of kinesiology courses. Based on the obtained results it can be concluded that the adaptation of the curriculum in accordance with the Bologna process has affected the quantitative and qualitative changes in the number of available courses which are preparing students for teaching in the physical and health educational field.
Keywords: Teaching Methodology of Physical Education; Kinesiology; teachers; preschool teacher